Malaysian national service: a study on the liability of the government towards the trainee in negligence cases / Shaiful Nizam Shahrin, Md Subri Hashim and Nurul Ain Badruddin - Shahrin, Shaiful Nizam; Hashim, Md Subri; Badruddin, Nurul Ain (2008)
Malaysia's national service program is now at a cross road, five years after its launch and many parents are in no hurry to send their children for the three-month stint. With a few accidents including death of the trainees been reported, most Malaysian, especially the parents still wondering on their rights in negligence cases. The aims of this study is to determine the extends of the government's liability for any negligence which incurred to the trainee at the camp training. The literature review (Chapter 2) provide the issues of national service which aims to develop the younger generation to become more patriotic and maintain the harmonious races in Malaysia and the duty of care of the government towards the trainee. Then, the legal chapters (Chapters 3) provide the national service legal frameworks in Malaysia which needs to comply by the trainer and the provision which made the government liable for his employee's negligence. The findings chapter (Chapter 4) reports on the fieldwork findings of respondent, conducted to investigate their perceptions of the Malaysian National service and to what extends the government would be liable for any negligence cases incurred to the trainee. The central arguments of this research is , there is a dire need to have a specific provision in National Service Training Act which provides the extends of the government liability towards the injuries sustained by the trainee and for any negligence act incurred at the camp training. The reason is to seek the public confidence especially the parents and the trainees on the implementation of the National Service Training Program which is not clearly mentioned about their right.